2018
DOI: 10.1029/2017jc013740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biological Production and Vertical Mixing on Sea Surface pCO2 Variations in the Changjiang River Plume During Early Autumn: A Buoy‐Based Time Series Study

Abstract: A monthlong, high-resolution buoy time series from the surface ocean of the Changjiang River plume in early autumn 2013 (30-min sampling frequency) shows great variability in the partial pressure of carbon dioxide (pCO 2 ) and other physical and biogeochemical parameters. Early in the deployment, surface pCO 2 decreased by~117 μatm in a single day (11-12 September, from an initial value of~527 μatm); a similar decline of 62 μatm occurred five days later (to~378 μatm). Both drawdown events were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 71 publications
(112 reference statements)
2
29
0
Order By: Relevance
“…Furthermore, we observed significant relationship between p CO 2 and Chl a with a slope value of −34.49 (supporting information Figure S2), which is close to that obtained using underway data in the East China Sea shelf (−49.8; Tseng et al, ). Very significant relationship between p CO 2 and DO was also observed (Figure c), which was similar to previous studies (Li et al, ; Zhai & Dai, ). Such significant relationships suggest the controlling effect of biological production on surface p CO 2 during Period III.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, we observed significant relationship between p CO 2 and Chl a with a slope value of −34.49 (supporting information Figure S2), which is close to that obtained using underway data in the East China Sea shelf (−49.8; Tseng et al, ). Very significant relationship between p CO 2 and DO was also observed (Figure c), which was similar to previous studies (Li et al, ; Zhai & Dai, ). Such significant relationships suggest the controlling effect of biological production on surface p CO 2 during Period III.…”
Section: Resultssupporting
confidence: 91%
“…Estuaries are challenging to fully understand because of the heterogeneity between and within estuaries that is driven by diverse processes operating on different time scales such as river discharge, nutrient and organic matter loading, stratification, and coastal upwelling (Jiang et al, 2013;Mathis et al, 2012). The traditional sampling method for carbonate system characterization involving discrete water sample collection and laboratory analysis is known to lead to biases in average pCO2 and CO2 flux calculations due to daytime sampling that neglects to capture diel variability (Li et al, 2018). Mean diel ranges in pH can exceed 0.1 unit and single day ranges can exceed 1 pH unit, with especially high diel variability in biologically productive areas or areas with higher mean pCO2 (Challener et al, 2015;Cyronak et al, 2018;Schulz and Riebesell, 2013;Semesi et al, 2009;Yates et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated that, despite estuaries representing <10 % of the domain area, interactions with shelf seas must be considered as the estuarine waters gave off more CO 2 than the shelves drew down. Eulerian studies in the estuarine zone have identified large tidal signals in pCO 2 with data collected from research vessels (Borges and Frankignoulle, 1999;Jeffrey et al, 2018a) and from moorings or fixed sites (Dai et al, 2009;Jeffrey et al, 2018a;Li et al, 2018;Bakker et al, 1996;Call et al, 2015;Ferrón et al, 2007;Santos et al, 2012). pCO 2 levels at the mouth of different rivers have been observed to co-vary with changes in river flow rate and with the tidal cycle (Ribas-Ribas et al, 2013;Canning et https://doi.org/10.5194/bg-2021-166 Preprint.…”
Section: Introductionmentioning
confidence: 99%